PERBANDINGAN ANTARA PENGGUNAAN ZAT PENGATUR TUMBUH (ZPT) EKSTRAK BAWANG MERAH DENGAN BOMBAY MERAH TERHADAP PERTUMBUHAN TANAMAN LIDAH BUAYA - Romandianty, Julzeti; Anggarani, Mirwa Adiprahara (AGRORADIX : Jurnal Ilmu Pertanian, 2024)
Aloe vera is a biopharmaceutical plant that is useful in the cosmetic, pharmaceutical and food sectors. Market demand for aloe vera increases every year, so it has the potential to be cultivated. However, aloe vera grows quite slowly. To overcome this, plants growth regulators (PGRs) are used in an effort to accelerate the growth of aloe vera. Shallots and red onions contain phytohormones in the form of auxin and gibberellin. This research aims to determine the comparison between shallots and red onions as natural PGRs in accelerating the growth of aloe vera. The research used a Randomized Block Design (RBD) with 2 factors, namely type of PGRs (shallots and red onions) and concentration (0%, 15%, 30%, 45%). The parameters observed were plant height, leaf circumference, number of leaves, and wet biomass. Data analysis using the two way ANOVA test followed by the DMRT test at the 5% level. The results showed that ZPT extract had a significant effect on all parameters except the number of leaves. Shallot ZPT extract with a concentration of 45% gives the best results.